Influence of Trichoderma harzianum and Bacillus thuringiensis with reducing rates of NPK on growth, physiology, and fruit quality of Citrus aurantifolia - Abdelmoaty, Salem; Khandaker, Mohammad Moneruzzaman; Mahmud, Khairil; Majrashi, Ali Abdullah; Alenazi, Mekhled Mutiran; Badaluddin, Noor Afiza (Instituto Internacional de Ecologia, 2022)
Continuous use of chemical fertilizers gradually shrinks the crop yield and quality, and these adverse effects can be reduced by adopting new sustainable practices such as the use of manure, biofertilizers, and nano fertilizers. Limited information is existed on the application of Trichoderma harzianum and Bacillus thuringiensis microbes to improve lemon seedlings growth, physiology, and fruit formation. Therefore, the current study is aimed to evaluate the effects of T. harzianum and B. thuringiensis microbes mixing with low levels of inorganic fertilizer (NPK) on the plant growth, development, and quality of limau nipis (key lemon) fruits. The lemon seedlings growing media were inoculated during transplanting with T. harzianum and B. thuringiensis at various NPK fertilizers under polybagged conditions. The seedlings were grown around eighteen (18) months after inoculation with biofertilizers followed by Randomized Complete Block Design (RCBD) with five (5) replications. The results showed that T. harzianum with 50 g of NPK treatment (T2) increased the seedling’s height, branch number, leaf height, ground area, and absolute growth rate (AGR) plant height by 50.12%, 107.84%, 17.91%, 17.91%, 116.93%, and 56.02%, respectively, over the control treatment. The number of leaves (60.82%), leaf area (42.75%), stem diameter (27.34%), specific leaf area (SLA) (39.07%), leaf area index (LAI) (54.40%), and absolute growth rate for leaf number (73.86%), leaf area (306.85%) and stem diameter (46.8%) of lemon seedlings increased significantly with B. thuringiensis plus 50 g NPK treatment (T3). The applications of B. thuringiensis with 25 g NPK fertilizer treatment (T5) increased leaf fresh weight (LFW), leaf dry weight (LDW), leaf moisture content (LMC), specific leaf weight (SLW), leaf relative growth rate (RGR), and chlorophyll content by 96.45%, 56.78%, 13.60%, 24.76%, 45.45%, and 16.22%, respectively, over the control group. In addition, T5 treatment increased the fruits number, individual fruit weight, fruit diameter, fruit dimension, leaf total soluble solids (TSS), and fruit TSS content of lemon tress by 81.81%, 55.52%, 43.54%, 25.69%, 89.47%, and 70.78% compared to the control treatment. Furthermore, soil inoculation of B. thuringiensis significantly increased the pulp to peel ratio and juice content of lemon fruits. From this study, it can be concluded that soil inoculation of both T. harzianum and B. thuringiensis with 25-50% NPK during transplanting improved plant growth, physiology, and fruit quality of limau nipis trees.